Biometry and auto-fluorescence of the anterior ocular segment in diabetics with and without autonomic neuropathy: a case control study. - Sparrow, J; Neil, H; Bron, A (1992)
The biometry and auto-fluorescence of the anterior ocular segment were examined in a case control study of two populations of diabetics. Cases, with diabetic autonomic neuropathy, and controls without neuropathy (forty in each group) were selected from a community based diabetic population and matched individually for age, sex, and type of diabetes. Scheimpflug and auto-fluorescence anterior segment photography were performed and analysed by digital image analysis in a masked fashion. There were differences between the groups in axial lens thickness, front radius of curvature of the lens, anterior chamber depth and lenticular auto-fluorescence. These findings are discussed in the context of the known association between autonomic neuropathy and narrow angle glaucoma, and possible common mechanisms of tissue damage in diabetes.